2005
DOI: 10.1080/16864360.2005.10738392
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Reconstruction for Medical-CAD Modeling

Abstract: Reverse engineering, the process of obtaining a geometric CAD model from measurements obtained by scanning an existing physical model, is widely used in numerous applications, such as manufacturing, industrial design and jewellery design and reproduction. For creating editable CAD models meant for manufacturing we identify that it is more appropriate to use feature-based constraint-based representations, since they capture plausible design intent. We propose this type of model representation for reverse engine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 20 publications
0
16
0
2
Order By: Relevance
“…The result of the study made by Tolouei-Rad [13] was suggested that the software choice must be tailored to the needs individually. In the study of Starly et al [11] researchers were evaluated the assessments on the creation stages of a 3D model and they found that reverse engineering gave better results compared with other software.…”
Section: Discussionmentioning
confidence: 99%
“…The result of the study made by Tolouei-Rad [13] was suggested that the software choice must be tailored to the needs individually. In the study of Starly et al [11] researchers were evaluated the assessments on the creation stages of a 3D model and they found that reverse engineering gave better results compared with other software.…”
Section: Discussionmentioning
confidence: 99%
“…However, the design has always been limited to such regular primitive shapes in the form of patterned straight lines, square or circular holes. This is primarily due to shortcomings of current CAD technologies either in representation of such micro-structures or the inability to transfer detailed microstructure information to SFF machines [14][15][16]. There is a need to expand the pore architecture variety to provide for better functionality and adequate nutrient supply into the interior of the scaffold.…”
Section: Introductionmentioning
confidence: 98%
“…Biomechanics work of human knee structure is successfully carried out after segmenting 2D medical images to design 3D model of human knee for analysis purpose [6], [7]. Reconstruction of CAD models and image extraction from 2D data has received significant attention [8]. Biomedical imaging is now universally accepted clinical course of action, and has became a part of future trends [9].…”
Section: Introductionmentioning
confidence: 99%